Earth pressure coefficients for design of geosynthetic reinforced soil structures - Castorina Silva Vieira (2011)
There are several methods proposed in the last two decades that can be used to design geosynthetic reinforced soil retaining walls and slopes. The majority of them are based on limit equilibrium considerations, assuming bi-linear or logarithmic spiral failure surfaces. Based on these failure mechanisms, design charts have been presented by several authors. However, the use of design charts is less and less frequent. The paper presents results from a computer program, based on limit equilibrium analyses, able to quantify earth pressure coefficients for the internal design of geosynthetic reinforced soil structures under static and seismic loading conditions. Failure mechanisms are briefly presented. Earth pressure coefficients calculated by the developed program are compared with values published in the bibliography. The effect of seismic loading on the reinforcement required force is also presented. To avoid the use of design charts and based on the obtained results, approximate equations for earth pressure coefficients estimation are proposed. The performed analyses show that the failure mechanism and the assumptions made have influence on the reinforcement required strength. The increase of reinforcement required strength induced by the seismic loading, when compared to the required strength in static conditions, grows with the backfill internal friction angle. The effects of the vertical component of seismic: loading are not very significant.